ANALYSIS OF THE RELATIONSHIP BETWEEN CHARACTERISTICS OF TEENAGERS AND FAMILY FUNCTIONS ON TEENAGERS’ BEHAVIOR FOR CONSUMING DRUGS IN EAST JAVA - Ismaini Zain; Erma Oktania Permatasari; Mardiyono Mardiyono; Amri Muhaimin; Dwilaksana Abdullah Rasyid (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2022)
This research aims to analyze the relationship between the characteristics of teenagers and family functions as well as the understanding of narcotics, psychotropics, and addictive substances on the behavior of teenagers consuming drugs in East Java as a response variable with a binary scale. The data source obtained through secondary data from the Performance Survey and Accountability Program 2019 with the observation unit teenagers aged 10-24 years. The sample used is 4,649. The analytical method used is descriptive statistics, the Chi-square method, and Odds Ratio (OR). The percentage of adolescent consuming drugs is 4.1% descriptively. The relationship analysis shows that the variables significantly related to young people's behavior in consuming drugs are gender, place of residence, level of education, age group, religious values, and psychological consequences. From the OR figures concluded that young males are 3.2 times more at risk of consuming drugs than young females. From the aspect of family function, it can be inferred that the percentage of young substance abusers from families who apply religious values is greater than those who do not. The findings of this research show that the risk of young people from families who practice religious functions becoming substance abusers are 1.61 times more compared to families who do not practice it. The understanding of drugs is not always related to teenagers' behavior in consuming drugs, because those who understand the psychological consequences of substance abuse are also 1.64 times more at risk of using drugs compared to teenagers who do not understand.